2020
DOI: 10.18632/oncotarget.27437
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of FANCD2 is associated with survival in ovarian carcinoma

Abstract: Objective: Ovarian cancer is a leading cause of death from gynecological cancers. Late diagnosis and resistance to therapy results in mortality and effective screening is required for early diagnosis and better treatments. Expression of the Fanconi Anemia complementation group D2 protein (FANCD2) is reduced in ovarian surface epithelial cells (OSE) in patients with ovarian cancer. FANCD2 has been studied for its role in DNA repair; however multiple studies have suggested that FANCD2 has a role outside the nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Previous studies have linked Fancd2 to susceptibility to cancer. Fancd2 is a key player in the DNA repair pathway and is important for maintaining genomic stability in response to various gene damage [ 13 ]. Recently, there are studies that up-regulation of Fancd2 expression is positively correlated with tumor size and poor prognosis in ovarian cancer, nasopharyngeal carcinoma, glioblastoma, and EC [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have linked Fancd2 to susceptibility to cancer. Fancd2 is a key player in the DNA repair pathway and is important for maintaining genomic stability in response to various gene damage [ 13 ]. Recently, there are studies that up-regulation of Fancd2 expression is positively correlated with tumor size and poor prognosis in ovarian cancer, nasopharyngeal carcinoma, glioblastoma, and EC [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lisa et al observed that high expression of Fancd2 promoted excessive proliferation and metastasis of esophageal squamous cell carcinoma cells [ 12 ]. Sonali et al suggested a correlation between subcellular localization of Fancd2 and ovarian cancer survival; and Fancd2 localized in the nucleus led to reduced patient survival [ 13 ]. Collectively, the role of Fancd2 in cancers is evident.…”
Section: Introductionmentioning
confidence: 99%
“…Since ATM is a DDR gene and functions through the phosphorylation of HRR-associated genes, namely ATR , RAD51 , FANCD2 , RPA2 , and BRCA1/2 among others [ 39 43 ], we investigated the expression of various HRR-associated genes and γH2AX in ATM -KO NGP and ATM haploinsufficient CHP-134 cells. We observed that the protein levels of FANCD2, RAD51, and ATR, which promote alternative end-joining, DNA damage repair, and cancer cell survival [ 44 , 45 ], were downregulated. In contrast, p21 and γH2AX levels increased in the ATM -deficient NB cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Also, studies conducted in the United Kingdom and Poland on ovarian carcinoma samples verified that the risk of recurrence and death are highly associated with the expression level of FANCD2 (Moes-Sosnowska, 2019; Mani, 2021). On the other hand, in the United States, a study conducted on 181 ovarian cancer patients provided evidence of an increased survival rate in patients with FANCD2 mutation (Joshi, 2020). On the basis of its upregulation, FANCD2 has an unsatisfactory prognosis for other types of cancer, which may contribute to tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%